2023
DOI: 10.3390/ijms24032941
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Analysis of MgO Nanoparticle-Induced Immunity against Fusarium Wilt in Tomato

Abstract: Fusarium wilt, caused by Fusarium oxysporum f. sp. lycopersici (FOL), is a devastating soilborne disease in tomatoes. Magnesium oxide nanoparticles (MgO NPs) induce strong immunity against Fusarium wilt in tomatoes. However, the mechanisms underlying this immunity remain poorly understood. Comparative transcriptome analysis and microscopy of tomato roots were performed to determine the mechanism of MgO NP-induced immunity against FOL. Eight transcriptomes were prepared from tomato roots treated under eight dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 50 publications
0
1
0
Order By: Relevance
“…It was shown that metal NPs can affect the level of expression of genes encoding the synthesis of the vacuolar proton exchanger, SOD, cytochrome P450-dependent oxidase, and PER, 153 miRNAs genes, 154 and genes encoding aquaporins in seeds. 155 Takehara et al 156 demonstrated that MgO NPs induce strong immunity against Fusarium wilt in tomatoes, which was associated also with differential expression of several genes and provided new insights into the probable genetic mechanisms explaining this immunity. However, we are unaware of studies on how Mn NPs effect gene expression, and such studies are obviously much needed.…”
Section: Effect On Plant Resistance To Biotic Stresses and Phytopatho...mentioning
confidence: 99%
“…It was shown that metal NPs can affect the level of expression of genes encoding the synthesis of the vacuolar proton exchanger, SOD, cytochrome P450-dependent oxidase, and PER, 153 miRNAs genes, 154 and genes encoding aquaporins in seeds. 155 Takehara et al 156 demonstrated that MgO NPs induce strong immunity against Fusarium wilt in tomatoes, which was associated also with differential expression of several genes and provided new insights into the probable genetic mechanisms explaining this immunity. However, we are unaware of studies on how Mn NPs effect gene expression, and such studies are obviously much needed.…”
Section: Effect On Plant Resistance To Biotic Stresses and Phytopatho...mentioning
confidence: 99%
“…Another recent study reported the molecular analysis mediated tomato immunity against fungal (fusarium wilt) disease. 104 Enrichment analysis using the Kyoto Encyclopedia of Genes and Genomes (KEGG) revealed that treatment with MgO NPs upregulated the Rcr3 encoding apoplastic protease and RbohD encoding NADPH oxidase when exposed to fusarium wilt infection. The gene encoding glycine-rich protein 4 (SIGRO4) was rapidly transcribed in tomato roots pre-supplemented with MgONPs.…”
Section: Mgo Nps Improve Biotic Stress Tolerance and Its Mechanismsmentioning
confidence: 99%
“…Viruses are also included, although they cannot live or reproduce on their own. These cells may require magnification to be seen but when cultured on solid media that allows their growth and multiplication; they form visible colonies consisting of millions of cells [8].…”
Section: Introductionmentioning
confidence: 99%